Ecosystem productivity has a stronger influence than soil age on surface soil carbon storage across global biomes - Plaza, César (2023)
Interactions between soil organic matter and minerals largely govern the carbon sequestration capacity of soils. Yet, variations in the proportions of free light (unprotected) and mineral-associated (protected) carbon as soil develops in contrasting ecosystems are poorly constrained. Here, we studied 16 long-term chronosequences from six continents and found that the ecosystem type is more important than soil age (centuries to millennia) in explaining the proportion of unprotected and mineral-associated carbon fractions in surface soils across global biomes. Soil carbon pools in highly productive tropical and temperate forests were dominated by the unprotected carbon fraction and were highly vulnerable to reductions in ecosystem productivity and warming. Conversely, soil carbon in low productivity, drier and colder ecosystems was dominated by mineral-protected carbon, and was less responsive to warming. Our findings emphasize the importance of conserving ecosystem productivity to protect carbon stored in surface soils.